The Obstacle Challenging SMEs Performance in Ogun State, Nigeria - Adejare Yusuff Aremu; Norhilmi Bin Muhammad (Training & Research Institute - Jeramba Ilmu Sukses, 2022)
This study presents a conceptual framework for determining the effects of Market Orientation, Entrepreneurial Orientation, and Information Technology on the performance of small and medium-sized firms (SMEs) in Nigeria. The resource-based value theory was used to explain the elements affecting SMEs' performance. Furthermore, this study’s conceptual framework is based on the data derived from a newly constructed questionnaire. 130 copies of the questionnaires were distributed to the CEO / director and managers of SME organisations in Ogun State, Nigeria. Out of the 210 questionnaires, half or 105 were returned and analysed. The Statistical Package for the Social Sciences (SPSS) software was used to analyse the empirical data. It was found that the performance of SMEs organizations is significantly influenced by two factors, market orientation and entrepreneurial orientation, while there is no significant relationship between information technology and SME performance. This study provides valuable input for SMEs organisations by helping them to strategise future operational plan in various industries, including the education sector. The main limitation of this study is that has a limited sample size, and it did not include external performance indicators outside of procurement. As these indicators could provide additional insight into the success of SMEs, future research could consider including them as variables.